Les débuts de la phraséologie et les premières « phraséologies historiques » italo-françaises - Autelli, Erica (Linguistik Online, 2022)
Phraseological studies are prospering, as there have been many important publications over the last years. However, while most researchers date phraseology studies back to Charles Bally (1909), they have a long tradition that has been ignored for years. Indeed, the term phraseology has been found in lots of works dating back centuries, even in the title of works going back to the 16th century (cf. also Autelli 2021a, 2021b). The main goals of this paper are to illustrate the concept of phraseology throughout the years and to investigate some of the works found, as they do not all look alike and still play an important role for terminology, phraseography and phraseodidactics. In particular, some of the most significant bilingual works (from the 19th and 20th century) based on French and Italian so-called “phraseologiae” (that contain terms such as “phraséologie” or “fraseologia” in the title of the works) will be analysed, as there are significantly more of them than in other languages.